Student Self-Efficacy is Viewed Through Parental Involvement, Teacher Support, and Peer Support - Laka, Laurensius; Suryanto, Suryanto (Bulletin of Counseling and Psychotherapy, 2024)
Self-efficacy influences students' beliefs to achieve the desired results. The social environment was vulnerable to the development of student self-efficacy because it functioned as a source of information that students perceived. This study aimed to analyze student self-efficacy in terms of parental involvement and teacher and peer support. These participants involved 400 SMK students in Pasuruan Regency, who were selected using a multi-stage random sampling technique. The research instrument used a self-efficacy scale with the test results producing a reliability coefficient of .780, parental involvement .785, teacher support .572, and peer support .834. Data analysis used PLS-SEM. Based on the probability value of F-statistics, the p-value was .000 < α (α = .05), meaning that there was an influence from the three predictor variables simultaneously on student self-efficacy. Partially, the t-statistical value of the three variables was also proven to be greater than the t-table (1.96), with parental involvement of 2.868, teacher support of 8,970, and peer support of 4,101. Thus, simultaneously, predictor variables had an effect on self-efficacy, and partially, teacher support had the most significant effect, followed by peer support, and parental involvement had the slightest effect.